2010
DOI: 10.1002/fuce.201000037
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Structural Change and Anisotropic Permeability in Compressed Carbon Cloth Polymer Electrolyte Fuel Cell Gas Diffusion Layers

Abstract: The effect of compression on the actual structure and transport properties of the carbon cloth gas diffusion layer (GDL) of a polymer electrolyte fuel cell (PEFC) are studied here. Structural features of GDL samples compressed in the 0.0–100.0 MPa range are encapsulated using polydimethylsiloxane (PDMS) and by employing X‐ray micro‐tomography to reconstruct direct digital 3D models. Pore size distribution (PSD) and porosity data are acquired directly from these models while permeability, degree of anisotropy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Ostadi, Rama et al investigated in LB simulations on GDL structures which were obtained from nano-computed tomography. They characterized the structure according to geometric characteristics, anisotropy and effects of compression [41,42,21,43,44,45,46]. As in the macrohomogeneous approaches mentioned before also the simulations on the reconstructed microstructure show the evidence of the non-isotropic transport properties on the behavior of the mass transport on higher spatial scales.…”
Section: Introductionmentioning
confidence: 84%
“…Ostadi, Rama et al investigated in LB simulations on GDL structures which were obtained from nano-computed tomography. They characterized the structure according to geometric characteristics, anisotropy and effects of compression [41,42,21,43,44,45,46]. As in the macrohomogeneous approaches mentioned before also the simulations on the reconstructed microstructure show the evidence of the non-isotropic transport properties on the behavior of the mass transport on higher spatial scales.…”
Section: Introductionmentioning
confidence: 84%
“…Their investigations show that doubling the anode GDL thickness with the increase in interior porosity (similar to the lower compression ratio) allows more liquid water transport through the membrane and out of the anode. Xray micro-tomography has been combined with Lattice Boltzmann numerical modelling [16] to analyse the pore-scale water transport behaviour under different compression levels. They suggested that the internal pressure exerted on the carbon cloth GDL should be within 0.3-10.0 MPa to achieve the optimum transport properties of a PEFC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, porous electrodes of PEMFC, especially their gas diffusion layers (GDLs), are practically under compression and deformation. . GDL, which is made from porous materials like carbon paper, plays a key role in a PEMFC performance via providing mass transfer and conductivity for the CL .…”
Section: Introductionmentioning
confidence: 99%